Staff Competence, Support Services, and VAT Collection Performance: Does Managerial Performance Mediate the Relationship? - Fakhari, Nabil Yousuf Mohammad; Din, Badariah Hj; Omar, Rusdi (South Asian Journal of Social Sciences and Humanities, 2022)
VAT collection is a major issue for several governments around the world. Different countries have applied different techniques to enhance VAT collection. Likewise, the UAE government has introduced VAT and its collection is challenging for them. One of the key issues that has been observed in the literature is that support services are limited, and the staff appointed for collection is incompetent and require proper training. Similarly, the managerial role at the same time cannot be ignored. Therefore, the purpose of the study is to identify the mediating role of managerial performance between staff competence, support services and VAT collection performance. For the said purpose, primary quantitative causal research has been conducted using adopted questionnaires. The findings of the study are based on structural equation modeling technique and contributed to Economic Theory of Tax Compliance by identifying the mediating role of managerial performance. The study is equally important for the practitioners in understanding the importance of boosting staff competence and provision of support services for enhancing VAT collection.